Pola Penanganan Warga Binaan Pelaku Kekerasan Seksual Anak di Bawah Umur Pada Rumah Tahanan Negara Kelas II B Kefamenanu - Eman, Riki Patrisius; Kalembang, Elpius; Naif, Imanuel (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2025)
This study aims to find out how the pattern of handling inmates of minor sexual violence in the state prison class II B Kefamenanu. The research method used is qualitative descriptive. The results of the study show that the coaching pattern carried out by the prison officers runs well in accordance with the coaching pattern that has been implemented where the inmates obey every regulation in the prison and always follow the coaching carried out. The skill development pattern shows that the inmates can master their skills so that they can develop these skills through handicrafts and make many forms of handicrafts such as tissue boxes, donation boxes, ashtrays and others. In conclusion, personality development, such as religion, nation, and legal awareness, is going well, while intellectual development has stopped because it is no longer applied in prisons. Patterns of skill development, such as independent businesses, small industries, and agriculture, have been going well. However, coaching according to talent is still constrained due to the lack of facilities and infrastructure in the detention center.